Teaching Digital Citizenship for Vocational Students through “Netizen” Application: its Urgency and Effectiveness - Wahyudi, Diki; Prihatin, Titi (Indonesian Journal of Curriculum and Educational Technology Studies, 2022)
This study aims to develop a mobile learning-based application, named Netizen, that supports students' independent learning. The research employs a developmental research approach, primarily utilizing the ADDIE instructional design model. The study's findings indicate a positive trend. Specifically, the validation of media and material experts at 84.67% and 96.67%, respectively, illustrates the feasibility of producing Netizen applications. The Wilcoxon test's results, with Asymp.Sig. (2-tailed) of 0.000, are less than <0.05, signifying a significant difference in the average scores of students before and after using the Netizen application. The effectiveness test results reveal a gain score of 0.7052 or 70.52%, classifying it as highly effective. In conclusion, the Netizen application can enhance students' learning processes and outcomes. Abstrak Studi ini bertujuan untuk mengembangkan aplikasi berbasis pembelajaran seluler, yang dinamakan Netizen, yang dapat mendukung pembelajaran mandiri siswa. Penelitian ini menggunakan pendekatan penelitian pengembangan, dengan menggunakan model desain instruksional ADDIE sebagai pendekatan utama. Hasil penelitian menunjukkan kecenderungan positif. Secara khusus, validasi dari ahli media dan ahli materi pada tingkat 84,67% dan 96,67%, masing-masing, menggambarkan kemungkinan untuk memproduksi aplikasi Netizen. Hasil uji Wilcoxon, dengan Asymp.Sig. (2-tailed) sebesar 0,000, kurang dari <0,05, menandakan perbedaan yang signifikan dalam skor rata-rata siswa sebelum dan setelah menggunakan aplikasi Netizen. Hasil uji efektivitas mengungkapkan skor kenaikan sebesar 0,7052 atau 70,52%, yang diklasifikasikan sebagai sangat efektif. Sebagai kesimpulan, aplikasi Netizen dapat meningkatkan proses pembelajaran dan hasil belajar siswa.